India Ink Staining, a Rapid and Affordable Test for Diagnosis of Cryptococcal Meningitis - Masfiyah, Masfiyah (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2015)
Cryptococcal meningitis incidence has increased along with an increase in incidence of HIV-AIDS. This infection causes increased morbidity and mortality in patients with HIV-AIDS. A rapid diagnosis plays an important role to ensure a prompt therapy of the disease. The cryptococcal polysaccharide antigen test for diagnosis of meningitis is rapid but relatively expensive while culture is time consuming. A 47-year man was admitted to hospital with a headache, fever, nausea, and vomiting and a HIV history for the last 6 months. On physical examination, he was compos mentis, meningeal’s stimuli signs (+), where as on examination of craniales nerves, motor and sensibility was in a normal range. Routine blood was normal, 60 CD4 cells/mm3. Laboratory finding included a clowdy/turbid Cerebrospinal fluid (CSF), low glucose level (CSF glucose 43 mg / dl vs. blood glucose 293 mg / dl), elevated protein concentration (137.1 mg / dl), and polymorphonuclear pleocytosis. India ink stain showed encapsulated yeasts. Cryptococcus sp is the only encapsulated yeast, while C. neoformans is the most common cause of Cryptococcosis in patients with HIV-AIDS. The patient was diagnosed with Cryptococcal meningitis by indian ink staining, and immediately given anti-fungal theraphy.